The association between crowding within households and behavioural problems in children: Longitudinal data from the Southampton Women’s Survey - Marsh, R; Salika, T; Crozier, S; Robinson, S; Cooper, C; Godfrey, K; Inskip, H; Baird, J (Wiley, 2019)
BACKGROUND:In England, nearly one child in ten lives in overcrowded housing. Crowding is likely to worsen with increasing population size, urbanisation, and the ongoing concerns about housing shortages. Children with behavioural difficulties are at increased risk of mental and physical health problems and poorer employment prospects. OBJECTIVE:To test the association between the level of crowding in the home and behavioural problems in children, and to explore what factors might explain the relationship. METHODS:Mothers of 2576 children from the Southampton Women's Survey population-based mother-offspring cohort were interviewed. Crowding was measured at age 2 years by people per room (PPR) and behavioural problems assessed at age 3 years with the Strengths and Difficulties Questionnaire (SDQ). Both were analysed as continuous measures, and multivariable linear regression models were fitted, adjusting for confounding factors: gender, age, single-parent family, maternal education, receipt of benefits, and social class. Potential mediators were assessed with formal mediation analysis. RESULTS:The characteristics of the sample were broadly representative of the population in England. Median (IQR) SDQ score was 9 (6-12) and PPR was 0.75 (0.6-1). In households that were more crowded, children tended to have more behavioural problems (by 0.20 SDQ points (95% CI 0.08, 0.32) per additional 0.2 PPR, adjusting for confounding factors). This relationship was partially mediated by greater maternal stress, less sleep, and strained parent-child interactions. CONCLUSIONS:Living in a more crowded home was associated with a greater risk of behavioural problems, independent of confounding factors. The findings suggest that improved housing might reduce childhood behavioural problems and that families living in crowded circumstances might benefit from greater support.